Toward a Connected City Accessibility Planning for Multimodal Transport Integration in Palembang - Paulina M Latuheru; Driaskoro Budi Sidharta; Tertib Sinulingga; Cut Adinda Nathasia; Budiharso Hidayat (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Palembang has three main modes of transportation operating separately: river transport, Bus Rapid Transit (BRT), and Light Rail Transit (LRT). Although these modes have great potential to complement each other, the lack of proper integration results in inefficiencies in public transportation services. This study employs a qualitative approach using descriptive methods. This approach is chosen to describe and analyze the actual conditions and potential integration between river transport, Bus Rapid Transit (BRT), and Light Rail Transit (LRT) in Palembang. Data were collected from field observations, in-depth interviews with relevant stakeholders, and literature studies. Based on the integration performance measurement, the Modal Interaction Matrix resulted in a Normalized Score of -200, which falls into the poor category. Several key challenges were identified, including unintegrated infrastructure, unsynchronized operational schedules, and separate ticketing systems.